Barriers to the effective integration of developed ICT for SMEs in Rural NIGERIA - Olusegun Sadiq; Dieu Hack-Polay; Ted Fuller; Mahfuzur Rahman (Businesses, 2022)
This study investigated three key factors (technological-related, organisational-related and environmental-related barriers) affecting the adaptation to or integration of developed ICT. It also examined how SMEs in less developed countries can explore the different stages of developed ICT by moving from one stage to the other. The integration of ICT in SMEs is important as technologies have become competitive tools in contemporary business practices. This study is based on a survey of 322 Nigerian SMEs which was successfully validated using the SmartPLS3 software. The quantitative analysis centred on the three hypothesised barriers to measure the extent to which SMEs' internal and external variables could limit their competitiveness in relation to business expansion and organisational growth. The analysis helped explain some of the critical challenges faced by rural SMEs in an emerging economy such as Nigeria despite the literature's previous emphasis on the impacts of ICT on the SMEs' growth and expansion. A major contribution of the study is the development of a distinct model to help SMEs identify the significance of developed ICT and propose a strategy for SMEs to navigate the stages of developed ICT.
Keywords: 650; ICT; SMEs; less developed countries (LDCs); Nigeria; developing country